2021
DOI: 10.1021/acs.nanolett.1c00915
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic Angstrom-Wide Conductive Channels in Black Phosphorus by Top-down Cu Intercalation

Abstract: Two-dimensional (2D) materials have received much attention in view of their superior properties and their exotic behavior both of which result from their atomic scale thickness 1,2 .To further improve and modulate these properties, various methods including substitutional doping, functionalization, and defect engineering have been explored [3][4][5] . Among these, intercalation has numerous advantages in that new optical, magnetic, electronic or even

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…As the previous studies reported, the copper atoms were successfully inserted into the lattice of the BP. [42,43] Since the cRP NRs has larger crystal plane distance, the inter calation of copper is more smoothly. After the intercalation, the inserted metal atoms are reacted with the phosphorus and are finally transformed into the metal phosphides.…”
Section: Resultsmentioning
confidence: 99%
“…As the previous studies reported, the copper atoms were successfully inserted into the lattice of the BP. [42,43] Since the cRP NRs has larger crystal plane distance, the inter calation of copper is more smoothly. After the intercalation, the inserted metal atoms are reacted with the phosphorus and are finally transformed into the metal phosphides.…”
Section: Resultsmentioning
confidence: 99%
“…Nerl et al proposed a novel way to control seed Cu atoms in BP surface using a standard e-beam lithography technique, which can be readily scaled in the semiconductor industry. 33,83 Through TEM imaging of the structures grown in multi-layered BP, all Cu atoms occurred along the [010] direction without any other growth direction observed, which strongly illustrates the growth of Cu in the template of the BP lattice. The addition of the unique chiral dimensionality and metallic nature of the Cu layers into BP to form novel nanohybrids material may endow BP with a range of potential applications in nanosensors, nanocatalysis and plasmonics.…”
Section: Bp-based Nanohybridsmentioning
confidence: 97%
“…Usually, due to the small atomic size, the alkali ion is chosen as the guest species for intercalation, which can significantly change the carrier density and even induce a crystal structure transition, hence affecting the material properties. Studies showed that interaction is orientation dependent for anisotropic materials, e.g., intercalated ions have a more favorable channel along ZZ direction in BP [193,194] . While due to the high reactivity of an alkali ion, the intercalated materials are unstable under an ambient condition.…”
Section: Alloying and Intercalationmentioning
confidence: 99%